Histopatološke značilnosti Barrettovega požiralnika - Jović, Viktor (Medicinski razgledi, 2010)
Barrett's esophagus is precancerous condition in which metaplastic change fromsquamous to glandular epithelium of distal tubular esophagus is encountered, as a result of chronic gastroesophageal reflux disease. Adenocarcinoma arises in 0,5-1 % of patients with Barrett's esophagus, with growing frequency in the western population. The developement of adenocarcinoma from Barrett's esophagus is slow and gradu al, starting from low-grade through high grade epithelial dysplasia. The aim of this article is to bring close the scope of morphological changes in glandular mu cosa in its gradu al evolution to adenocardnoma to medical students, espedally in light ofgrowing number of control biopsies during endoscopic follow-up of patients with Barrett's esophagus.
Keywords: diagnostika; požiralnik; Barrettov požiralnik; gastroezofagealni refluks; histopatologija; therapy; zdravljenje